Speech perception: Auditory and visual cue integration in children with and without phonological disorder in voiceless fricatives - de Assis, Mayara Ferreira [UNESP]; Berti, Larissa Cristina [UNESP] (Taylor & Francis, 2025)
The literature reports contradictory results regarding the influence of visual cues on speech perception tasks in children with phonological disorder (PD). This study aimed to compare the performance of children with (n = 15) and without PD (n = 15) in audiovisual perception task in voiceless fricatives. Assuming that PD could be associated with an inability to integrate phonological information from two sensory sources, we presumed that children with PD would present difficulties in integrating auditory and visual cues compared to typical children. A syllable identification task was conducted. The stimuli were presented according to four conditions: auditory-only (AO); visual-only (VO); audiovisual congruent (AV+); and audiovisual incongruent (AV-). The percentages of correct answers and the respective reaction times in the AO, VO, and AV+ conditions were considered for the analysis. The correct percentage of auditory stimuli was considered for the AV- condition, as well as the percentage of perceptual preference: auditory, visual, and/or illusion (McGurk effect), with the respective reaction time. In comparing the four conditions, children with PD presented a lower number of correct answers and longer reaction time than children with typical development, mainly for the VO. Both groups showed a preference for auditory stimuli for the AV- condition. However, children with PD showed higher percentages for visual perceptual preference and the McGurk effect than typical children. The superiority of typical children over PD children in auditory-visual speech perception depends on type of stimuli and condition of presentation.
Keywords: Audiovisual speech perception; identification task; phonological disorder